Climate change, natural disasters and migration: An empirical analysis in developing countries - Alassane Drabo; Linguère Mously Mbaye (Institute for the Study of Labor (IZA), 2011)
The aim of this paper is to assess the relationship between natural disasters caused by climate change and migration by examining migration rates and levels of education in developing countries. Many studies such as the Stern review (2007) or the Intergovernmental Panel on Climate Change (IPCC, 2007) predict an intensification of climate change for future years. Thus climate change has taken an essential place in world governance. The relationship between climate change, natural disasters and migration is crucial; developed countries need to manage the increasingly complicated issues of additional incoming migratory flows caused by environmental degradation. We investigate this relationship by using panel data from developing countries in order to see the effect of natural disasters on migration rates and how that varies according to the level of education. Estimations are made with a country fixed effects estimator through an accurate econometric model. The results confirm previous studies, namely that natural disasters are positively associated with emigration rates. But beyond this result, the main contribution of this paper is to show that natural disasters due to climate change exacerbate the brain drain in developing countries characterized by the migration of highly skilled people just when those countries are at their most vulnerable and need greater support from skilled workers to deal with the damage associated with natural disasters. The paper also shows that this effect varies depending on geographical location.
urn:nbn:de:101:1-20110927559
Keywords: O15; Q54; 330; climate change; natural disasters; migration; Klimaveränderung; Naturkatastrophe; Auswanderung; Brain Drain; Internationale Wanderung; Entwicklungsländer